Effect of Oxidizers on Sulphide Removal from Hair Dissolving Liming Wastewater in Tannery - Hashem, Md Abul; Zaman Khan, Mst Nazmin; Roy, Protima; Hasan, Md Anik (Journal of Engineering Science, 2022)
Liming and unhairing is the conventional operation in the tannery where raw animal skins are treated with sodium sulphide and calcium hydroxide to remove keratin proteins e.g., hair and wool epidermis and to dissolve nonstructural proteins. The hair dissolving liming process discharges wastewater containing soluble sulphide. In acidification, the sulphide in wastewater generates toxic hydrogen sulphide, which has a negative impact on the environment. In this present study, the efficiency of hydrogen peroxide (H2O2) and sodium chlorite (NaClO2) oxidizers are compared to remove sulphide from the hair dissolving liming wastewater. The soluble sulphide in the raw liming wastewater was 3666 mg/L. At optimized dose and pH for H2O2 and NaClO2 soluble sulphide in the solution were 109.2 and 54.6 mg/L, respectively. The sulphide removal efficiency for H2O2and NaClO2 were 97.0% and 98.5%, respectively at an optimum pH (pH 7). Before and after treatment the physicochemical parameters of the liming wastewater were analysed by observing different water quality parameters viz: pH, TDS, EC and salinity. At optimized condition TDS and salinity removal efficiency was 47.2%, 52.3% and 8.1%, 11.2% for H2O2 and NaClO2, respectively. This simple and easy method would be effective for treating hair dissolving liming wastewater in reducing soluble sulphide discharge from the tanneries. Journal of Engineering Science 12(3), 2021, 67-72